Consideraciones sobre el nivel óptimo de reservas internacionales para Bolivia: 2003-2009 - Sergio Cerezo Aguirre (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2010)
– In recent years, Bolivia has accumulated a significant level of international reserves due to favorable external environment and the exchange rate regimen (crawling peg). In this context arises the question of: Which one is the optimal level of international reserves? According to the traditional indicators of adequacy of reserves and according to a model that shows the role of the reserves as a reliever of adverse external shocks, optimal reserves are located below the actual saved in the central bank since 2007. This result holds even when gold and non-financial public sector deposits of foreign currency at the central bank are excluded from the actual reserves. However, a sensitivity analysis shows that optimal reserves may increase considerably if some macroeconomic fundamentals change.
Keywords: F31; F32; F41; 330; Währungsreserven; Zahlungsbilanz; Währungssubstitution; Bolivien